Mitigation of soil loss from turfgrass cultivation by utilizing poultry abattoir sludge compost and biochar on low-organic matter soil. Issue 4 (10th February 2020) - Ozdemir, Saim; Nuhoglu, Nejlet Nusret; Dede, Omer Hulusi; Yetilmezsoy, Kaan
ABSTRACT: Commercial turfgrass cultivation is one of the main ornamental industries world-wide; however, successive turfgrass sod cutting from the same site removes surface soil, leading to a decline in soil organic matter, impairment of soil fertility and degradation of environment. The present study was aimed to investigate the applicability of poultry abattoir sludge compost (PASC) and biochar (BC) on the establishment of turfgrass by evaluating plant growth performance and mitigation of soil loss by organic waste amendments. The experimental study was designed on the soil which had originally low-organic matter content and previously used as a turfgrass sod harvested site in a sandy loam soil. Incorporation of PASC to soil improved the physicochemical properties in terms of bulk density (BD), water holding capacity (WHC), cation exchange capacity (CEC), pH, total nitrogen, total organic carbon (TOC), and organic matter (OM) by 37 (±2)%, 45 (±3)%, 55 (±3)%, 21 (±2)%, 48 (±2)%, 90 (±10)%, and 96 (±4)%, respectively. PASC-amended treatments enhanced the turfgrass growth rate more than the BC due to its increased nutrient availability. Incorporation of 100 Mg ha –1 (mega gram per hectare) PASC in surface soil with or without BC decreased the mineral soil removal rate by half of the respective soil (control) treatments. The results of the present study confirmed the utilization of PASC and BC as promising agro-industrial-based fertilizers in turfgrass sod production for sustainable soil and nutrient management. GRAPHICAL ABSTRACT: